2016
DOI: 10.1007/s00467-016-3324-6
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric combined liver–kidney transplantation: a single-center experience of 18 cases

Abstract: Pediatric CLKT provides encouraging results in the long term, even in the youngest patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 35 publications
3
31
0
Order By: Relevance
“…Our long‐term results of eGFR are better or comparable to other pediatric CLKT single‐center studies . In two of these studies, eGFR was around 70 mL/min/1.73 m 2 at last evaluation with varying follow‐up times . However, the follow‐up times were, on average, shorter than in our cohort.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Our long‐term results of eGFR are better or comparable to other pediatric CLKT single‐center studies . In two of these studies, eGFR was around 70 mL/min/1.73 m 2 at last evaluation with varying follow‐up times . However, the follow‐up times were, on average, shorter than in our cohort.…”
Section: Discussionsupporting
confidence: 76%
“…One-, five-, and ten-year patient survivals (95% CI) for pediatric patients were 91% (51% to 99%), 91% (51% to 99%), and 81% (42% to 95%), and one-, five-, and tenyear patient survivals (95% CI) for adult patients were 100%, 96% (73% to 99%), and 70% (44% to 85%) Our long-term results of eGFR are better or comparable to other pediatric CLKT single-center studies. 15,[27][28][29] In two of these studies, eGFR was around 70 mL/min/1.73 m 2 at last evaluation with varying follow-up times. 27,28 However, the follow-up times were, on average, shorter than in our cohort.…”
Section: Other Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the CLKT reports have been on cases from single deceased donors. For SLKT cases, most often one of the organs is procured from a living donor and the other from a deceased donor . Reports about CLKT and SLKT from a single living donor are limited from countries where a shortage of deceased donors remains a problem .…”
Section: Discussionmentioning
confidence: 99%
“…Success with combined liver‐kidney transplant has significantly improved recently, where an overall survival rate of 78.6% has been reported in those in whom the combined transplant was performed for an underlying metabolic condition . Even in the very small pediatric patients, an excellent survival rate approaching 90% and comparable to that in larger children can be attained in specialized centers . Others, including Niemi et al, have already suggested that LKT is effective and should be recommended in patients with chronic kidney disease .…”
Section: Discussionmentioning
confidence: 99%